ESTIMATION OF CROP WATER REQUIREMENT AND CROP COEFFICIENT OF TOMATO CROP USING METEOROLOGICAL DATA IN PAMPAIDA MILLENNIUM VILLAGE, KADUNA STATE, NIGERIA - Ahmed, A.; Oyebode, M. A.; Igbadun, H. E.; Oiganji, Ezekiel (FUDMA JOURNAL OF SCIENCES, 2020)
This report presents a study of crop water requirement and crop coefficient (Kc) for Tomato crop cultivated under irrigation in Pampaida Millennium Village Cluster, Ikara Local Government Area of Kaduna State, Nigeria, during the 2009/2010 dry season. A total of 7 tomato farmers were selected out of 45 farmers for the assessment exercise. Water applied per irrigation and soil moisture contents before and after irrigation was monitored throughout the seasons, while Tomato bulbs were harvested at the end of season and weighed. Average crop water use were estimated from the soil moisture content using the gypsum block, while daily reference Evapotranspiration (ETo) were computed from weather data using method Hargreaves equation. Crop coefficient values (Kc) were computed as the ratio of crop water use to ETo. The values of crop coefficients and seasonal crop water requirement per irrigation for different growth stages were determined, the computed *Kc values for different growth stage for the tomato crop grown in the study area was found to be between 0.77-1.15, the initial stage (*Kc =0.81; 20 mm/irrigation), crop development stage (*Kc = 1.09; 28 mm/irrigation), mid-season (*Kc = 1.15; 29 mm/ irrigation) and Late stage (*Kc = 0.77; 19 mm/irrigation), hence the mid-season gave the highest Kc value. However, the crop seasonal water requirement was found to be 386mm, which was within the recommended range. The crop coefficients and seasonal water requirement estimated in this study are reliable and could be used in irrigation design and scheduling for Tomato in the study area.